Improving mothers’ knowledge through educational videos in supporting adolescent girls during menarche - Nur Azizah Indriastuti; Nifta Aulia Ramadhanti; Riski Oktafia; Yuni Purwati; Siti Roshaidai Mohd Arifin (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2026)
Menarche is a significant developmental milestone requiring physical and psychological preparation. Mothers play an essential role in supporting adolescent girls through adequate information, guidance, and emotional support. This study aimed to evaluate the effectiveness of educational videos in improving mothers’ knowledge regarding menarche support. A pre-experimental one-group pretest–posttest study was conducted among 50 mothers selected through total sampling. Participants received video-based education covering menarche, pubertal changes, menstrual hygiene, communication, and supportive strategies, followed by brief discussions. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed an improvement in maternal knowledge, with the proportion of participants having good knowledge increasing from 56.0% to 96.0%. The median knowledge score increased from 14.5 to 16.0, with a significant difference between pre- and post-intervention scores (Z = 5.086, p < 0.001) and a large effect size (r = 0.872). Educational videos were effective in enhancing mothers’ knowledge and may serve as a practical strategy for strengthening maternal support during adolescent girls’ transition to menarche. Integration of video-based reproductive health education into school and community programs is recommended, with further research involving larger samples, control groups, and longer follow-up periods.